Talent development environments in sport in selected African countries as perceived by young elite football players - Tachom Waffo, B.; Hauw, D. (International Journal of Sport and Exercise Psychology, 2026)
Most African football nations need to strengthen their talent development environments (TDEs) in sport in order to nurture young elite players at the level of global competitiveness. However, despite the established importance of the environment to the striving and thriving of athletes, studies on TDEs in African football academies are scarce. This study`s objectives were twofold: (a) to test the reliability of the French version of the TDEQ-5 across three representative French-speaking African countries: Morocco (North Africa), Cameroon (Central Africa) and Côte d`Ivoire (West Africa), and (b) to assess and compare the quality of their TDEs in football. A sample from the three African countries selected consisted of 504 male academy footballers aged between 10 and 23, who completed the French version of the TDEQ-5. Confirmatory factor analysis and internal consistency analysis revealed a fair model fit of the TDEQ-5, therefore allowing its use in this context. However, the TDEQ-5`s factor of social support network was omitted in the comparisons because of low internal consistency. For the remaining four TDEQ-5 features, Moroccan players had the most favourable perception, while Cameroonian and Ivoirian players shared similar and less favorable perceptions of their TDEs. Across the selected countries, long-term development focus and holistic quality preparation were a strength and an area of improvement respectively. These findings suggest that the TDEQ-5 tends to validate differences and similarities in TDEs in sport between North, Central, and West African countries. It thus emerges as a reliable instrument to monitor and support the talent development journey of African academy footballers.